1979
DOI: 10.1177/014616727900500206
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Power and Tonic Heart Rate Responses to Psychosocial Stressors

Abstract: The aerobic power of 41 male and 29 female introductory psychology students was measured. They were then subjected to a series of psychosocial stressors. Tonic heart rate was used as the criterion variable. Aerobic power was found to be significantly (p < .001) related to how quickly subjects recovered from stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
1

Year Published

1983
1983
1992
1992

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 4 publications
3
26
1
1
Order By: Relevance
“…The difference in heart rate recovery seen here replicates previous reports (18,19), which have linked physical fitness with more rapid physiological recovery from psychosocial stress. The Spielberger State findings represent the first demonstration of an altered subjective response to an acute psychosocial stressor in trained versus untrained individuals: pre to post scores were unchanged for untrained subjects whereas scores for trained subjects declined significantly.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The difference in heart rate recovery seen here replicates previous reports (18,19), which have linked physical fitness with more rapid physiological recovery from psychosocial stress. The Spielberger State findings represent the first demonstration of an altered subjective response to an acute psychosocial stressor in trained versus untrained individuals: pre to post scores were unchanged for untrained subjects whereas scores for trained subjects declined significantly.…”
Section: Discussionsupporting
confidence: 91%
“…Studies employing heart rate (18) and skin conductance (19) measures, have found that fitness level did not affect the magnitude of response to a stressor, but was related to more rapid return to baseline following stressor termination. Although consistent with the hypothesis that aerobic fitness influences emotional reactivity, the findings have been limited to a single response modality and thus provide little information on overall reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…One approach involves monitoring psychophysiologic changes during the performance of contrived psychosocial stressors in the laboratory (6)(7)(8)(9)(10)(11)(12)(13). A second approach employs self-report measures of perceived life stress and stress-related symptomatology (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…One set of experiments (7)(8)(9)(10) has found that although trained and untrained individuals do not differ in their psychophysiologic response to laboratory stressors, trained subjects exhibit a faster recovery to baseline following termination of stress.…”
Section: Introductionmentioning
confidence: 99%
“…Ogsa Dienstbier et al (1981), Cox et al (1979) og Eliot et al (1976) har fra forskellige vinkler demonstreret, at udholdenhedstr~~ening har en fysiologisk effekt, der modarbejder effekten af psykisk (emotionel) stress.…”
Section: Resultater Og Diskussionunclassified